Perencanaan Perencanan Struktur Beton Bertulang Pada Gedung Sewa Perkantoran 7 Lantai Tahan Gempa Dengan Sistem Ganda Di Jalan Jendral Ahmad Yani Kota Pontianak - Rizki Falah, Andi Muhammad; Ramadhansyah Pulungan, Anugrah Prima; Anggraini, Irene; Sasongko, Hartanto Wahyu (Politeknik Negeri Jakarta, 2025)
The planning of rental office buildings in Pontianak City is an effort to minimize horizontal land use and prevent new issues, such as land crises. The structural planning carried out certainly needs to pay attention to several aspects, one of which is the influence of earthquakes. Essentially, earthquakes tend to impact structures at their joints; thus, reinforced concrete structures are designed using a moment-resisting frame system with a strong column-weak beam concept, combined with shear walls, referred to as a dual system. This design allows the structure to mitigate earthquake vibrations. The 7-story rental office building is located on Jl. Jendral Ahmad Yani, Bansir Laut, Kec. Pontianak Tenggara, Pontianak City, West Kalimantan Province. The earthquake load was planned to use the 2019 Indonesia Earthquake Map and the response spectrum method in accordance with SNI 1726-2019. Load calculations followed SNI 1727-2020, while the design of reinforced concrete structures for building construction complied with SNI 2847-2019. The analysis of the requirements and stability of the structure against the earthquake load by the spectrum response method has met the requirements and stability as an earthquake-resistant structure with a dual system. The maximum inter-level deviation that occurred was 8.411 mm for the x direction and 4.815 mm for the y direction.